2003
DOI: 10.1093/molbev/msg137
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Divergence of Microsatellite Abundance Among Species of Drosophila

Abstract: Among major taxonomic groups, microsatellites exhibit considerable variation in composition and allele length, but they also show considerable conservation within many major groups. This variation may be explained by slow microsatellite evolution so that all species within a group have similar patterns of variation, or by taxon-specific mutational or selective constraints. Unfortunately, comparing microsatellites across species and studies can be problematic because of biases that may exist among different iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 52 publications
7
51
0
Order By: Relevance
“…In general, heterozygosity and variance in repeat unit length are high in all populations (Table 1), similar to other Drosophila species for which dinucleotide repeat microsatellites have been assayed in natural populations (Hutter et al 1998;Noor et al 2000;Pascual et al 2000;Ross et al 2003;Orsini and Schlotterer 2004). We used a univariate ANOVA to test for differences among populations in levels of expected heterozygosity and variance in repeat unit.…”
Section: Resultsmentioning
confidence: 75%
“…In general, heterozygosity and variance in repeat unit length are high in all populations (Table 1), similar to other Drosophila species for which dinucleotide repeat microsatellites have been assayed in natural populations (Hutter et al 1998;Noor et al 2000;Pascual et al 2000;Ross et al 2003;Orsini and Schlotterer 2004). We used a univariate ANOVA to test for differences among populations in levels of expected heterozygosity and variance in repeat unit.…”
Section: Resultsmentioning
confidence: 75%
“…This increase is correlated with the larger size of the soybean genome and also with the fact that the public genome sequence data for soybean is enriched in RFLP-derived genomic clones relative to the other species we analyzed. Although it is uncertain whether either of these factors is causal to the increased frequency of class I SSRs in soybean data, it is noteworthy that Ross et al (2003) have recently described the rapid divergence of microsatellite abundance among closely related species. Wierdl et al (1997;and more recently Kruglyak et al 1998;Katti et al 2001) proposed that the lower frequency of long vs. short SSRs may result from selection against mutagenic sites in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Unequal recombination between SSRs and slip-mispairing during DNA replication (Sia et al 1997) result in polymorphism rates that tend to be much greater than those observed for nonrepetitive DNA sequences. The high rate of mutation combined with low selection coefficients on variant alleles result in extreme allelic diversity at microsatellite loci (Ross et al 2003).…”
mentioning
confidence: 99%
“…This species also specializes on particular host cacti endemic to the inhospitable Sonoran Desert, and offers the opportunity to address issues of adaptation to harsh dietary chemicals (Fogleman and Danielson 2002) and to thermal extremes (Stratman and Markow 1998). At this time a large microsatellite library is available (Ross et al 2003) that is being used to construct a genetic map for D. mojavensis. A cDNA library has also been constructed for use in producing a microarray.…”
Section: Drosophila Mojavensismentioning
confidence: 99%